Extending Research on the “War on Cops”: the Effects of Ferguson on Nonfatal Assaults Against U.S. Police Officers - Shjarback, John A. (Crime & delinquency, 2021)
This study tests whether violence directed toward American law enforcement has increased in the wake of events in Ferguson, Missouri, in summer 2014. Using monthly data from the Federal Bureau of Investigation’s (FBI) Law Enforcement Officers Killed and Assaulted (LEOKA) reports (2010-2016), we carried out time-series analyses to examine trends in nonfatal assaults on police officers in a sample of 4,921 agencies. Neither injurious nor noninjurious assaults on officers increased following Michael Brown’s death in August 2014. The findings are robust across a variety of model specifications and estimation techniques, providing little evidence of a “War on Cops” through 2016. The study adds empirical rigor to an ongoing national debate based largely on speculation/anecdotes. The impact and potential consequences of the current climate for officers’ perceptions of safety/risk are discussed.